Dual-energy computed tomography colonography using dual-layer spectral detector computed tomography: Utility of virtual monochromatic imaging for electronic cleansing. Issue 108 (November 2018) - Taguchi, Narumi; Oda, Seitaro; Imuta, Masanori; Yamamura, Sadahiro; Yokota, Yasuhiro; Nakaura, Takeshi; Nagayama, Yasunori; Kidoh, Masafumi; Utsunomiya, Daisuke; Funama, Yoshinori; Baba, Hideo; Yamashita, Yasuyuki
Highlights: Tagging density on VMI at low keV was significantly higher than that on 120 kVp. VMI can improve the image quality and electronic cleansing performance. Dual-layer spectral detector CT allows need-based retrospective tagging calibration. Abstract: Objective: To assess the utility of virtual monochromatic imaging (VMI) using a dual-layer spectral detector CT for electronic cleansing in fecal-tagging CT colonography (CTC). Methods: This study included 35 patients who underwent fecal-tagging CTC with a dual-layer detector spectral CT scanner. Conventional images at 120 kVp and VMI at 40, 50, and 60 keV were reconstructed. Quantitative image quality parameters, i.e., tagging density and image noise, were compared and the visual image quality was scored on a four-point scale. We recorded the number of the colon segments with appropriate tagging density (≥300 HU) for each patient and used these data to compare the reconstructions. In addition, electronic cleansing performance was semi-quantitatively assessed using a four-point scale. Results: The mean tagging density on VMI was significantly higher than that on conventional 120 kVp images. The number of colon segments with appropriate tagging density on VMI were significantly higher than that on conventional 120 kVp images. There was no significant difference among the reconstructed images with respect to image noise. Scores for subjective image quality and electronic cleansing performance on VMI were significantly higher than those on conventional 120 kVp images. Conclusion: With dual-layer spectral detector CT, VMI can yield significantly better fecal-tagged CTC image quality and improve electronic cleansing performance.